The impact of Coronavirus Disease 2019 on maxillofacial surgery training in Portugal - Gomes de Oliveira, Pedro (2024)
Introduction: The COVID-19 pandemic has forced Portuguese healthcare institutions to adapt management protocols and prioritize resources. These adjustments had a significant impact, affecting both clinical care and also training programs. The aim of this study was to access the maxillofacial surgery resident's perspective on the pandemic's impact on specialty training. Methods: We designed a nationwide questionnaire to evaluate surgical activity of maxillofacial surgery residents, the impact on surgical training and the perceived effect on their future. Results: We collected results of all maxillofacial surgery residents currently in training. Three out of 32 reported a decline in surgical activity of 90–100%, 11 stated a reduction of 75%, 12 expressed a decrease of 50% and 6 described a decline of 25%. Discussion: The majority of residents stated the need to consider an extension of training time. Alternative training tools such as virtual activities and simulation training should be considered as formal complements to residency programs. Conclusion: We found a significant decrease in surgical activity among all trainees coupled with a unanimous concern regarding their training progression.